Anti Gallai Fuzzy Graphs in Corona Graphs - G. Karlmarx, M. Kaliraja (International Journal of Advanced Science and Technology, 2020)
In this paper, we investigate about the anti Gallai fuzzy graphs ((G)) in corona graphs. Also we have analyzed some theorems, structure and domination number of that anti - Gallai graphs.